Comparison of Nonlinear Dynamics of Heart Rate Variability Between Conventional Cardiac Rehabilitation and Dance-Based Therapy: A Non-Randomized Crossover Clinical Trial - Silva, Joao Pedro Lucas Neves [UNESP]; Soares, Julio Cesar de avila [UNESP]; Laurino, Maria Julia Lopez [UNESP]; Ribeiro, Felipe [UNESP]; Gervazoni, Natacha de Lima [UNESP]; Alves, Bruna Izadora Spinardi [UNESP]; Moreira, Eduarda Carvalho Novaes [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Lorenconi, Roselene Modolo Regueiro [UNESP] (Sage Publications Inc, 2025)
Introduction: Dance has been suggested as an alternative therapeutic modality in cardiac rehabilitation programs (CRP). Therefore, evaluating the physiological responses of the body during dance is necessary to provide information that will allows it to be practiced a safe and effective way. In this context, the objective of the current study was to evaluate and compare the cardiac autonomic modulation (CAM) of women with cardiovascular risk factors (CRF) during and after a dance-based cardiac rehabilitation session and a conventional cardiac rehabilitation session. Methods: In total, 19 women, with at least 1 CRF, participated in this non-randomized crossover clinical trial, consisting of 4 steps: I. Familiarization with the dance protocol (DP); II. DP session; III. Familiarization with the conventional protocol (CP); IV. CP session. The CAM was evaluated using heart rate variability, considering nonlinear methods: recurrence plot, debugged trend fluctuations, and symbolic analysis. For data evaluation, 2-way analysis of variance for repeated measures was used, P < .05. Results: During exercise, an effect of protocol was observed for most of indices. In the DP, higher values were recorded for DET, Alpha-1, and 0 V% indices, and lower values for 1 V% and 2 ULV% indices and for entropy measurements. During recovery, no differences were observed between protocols. Effects of the exercises were observed in the comparisons between moments for all indices, however, a similar pattern of recovery was found between DP and CP. Conclusions: Comparisons of the dance and conventional protocols revealed that CAM was similar in both approaches, while greater alterations in nonlinear dynamics were observed during the DP exercise. However, these alterations were not able to modify the recovery of the volunteers. Clinical Trial Registration: The study was previously registered on the clinicaltrials.gov platform under registration number: NCT04967235. https://clinicaltrials.gov/study/NCT04967235?locStr=Brazil&country=Brazil&cond=Cardiovascular%20risk%20factors&term=Heart%20Rate%20Variability&intr=Dance%20therapy&rank=1
Keywords: therapy through dance; risk factors; cardiac rehabilitation; autonomic nervous system; nonlinear dynamics